The role of symbols in the mainstream to access literacy - Pampoulou, Eliada; Detheridge, Cate (My University, 2007)
Although theories in the past claimed that in order to be literate someone has to acquire specific prerequisite skills, more recent theories suggest that for some aspects of language, symbols can help people to access literacy. In this paper, we speculate that symbols can help children in schools to cope with their difficulties with print. Widgit Literacy Symbols have been developed over the last 20 years as a means of enhancing access to written communication and curriculum. Through the Symbol Inclusion Project (SIP), Widgit Software has been working closely with teachers in Warwickshire, creating resources for students in schools. Anecdotal evidence from the SIP project suggests that symbols can help children to anticipate their difficulties with literacy as well as to increase their motivation and self-esteem and improve their behaviour. © 2007, Emerald Group Publishing Limited
Keywords: Assistive technologies; Meaning from text; Print awareness; Symbols; Text comprehension